Studi Analisis Serbuk dengan Teknik Krim Silikon Menggunakan Plasma Tekanan Tinggi yang Diinduksi oleh Laser Nd: YAG - Madjid, Syahrun Nur (Jurnal Rekayasa Kimia & Lingkungan, 2012)
Laser-Induced Breakdown Spectroscopy (LIBS) is a technique that used for quantitative elemental analysis of various samples in different forms. In this technique, a laser light is focused on the surface of sample yielding a plasma just above the sample surface that used for analytical source. Nowadays, rapid powder analysis in tiny amount (mg) has been carried out using plasma induced by high power laser of Nd:YAG (Neodymium-doped Yttrium Aluminium Garnet) at atmospheric pressure. However, powder analysis using high power laser is still difficult to be carried out due to blow of powder when irradiated laser beam focused on a powder sample. In general, the powder must be transformed into pellet form prior to analysis. Pellet sample requires a lot of powder and it takes time for preparation. In this study, we developed a technique of powder sample with its size about 30 m ( 5 mg) that mixed with silicon grease ( 5 mg) that act as a binder. The mixed sample then thinly painted on the metal plate as sub-target. The study showed that by employing sillicon grease technique, a semiquantitative analysis of several elements contain in coal, rock, and water can be conducted. Meanwhile heavy metal in soils is still not able to detect. This results showed that sillicon grease technique using Nd:YAG laser can be applied for rapid semi-quantitative analysis of powder samples available only in tiny amounts.Keywords: high pressured plasma, Nd:YAG laser, powder analysis, silicon grease technique